Romania, between the "magnetism” of Structural Funds and the "corrective” tools of EU state aid regulations - Gabriela Dragan (European Regional Science Association (ERSA), 2005)
The paper intends to explain the relevance of the acquis communautaire on state aid in the context of Romanian regional policy-making. EU state aid regulations impose a number of restrictions on regional aid spending, which in their combination are intended to concentrate and modulate overall spending within priority areas. The paper reviews the Romanian legal, institutional and procedural frameworks on state aids and briefly analyses the main financial support schemes designed by the Romanian authorities to support regional development. The information presented in this paper are based on a more exhaustive research project which I coordinated in the framework of a Phare Project (see: Gabriela Dragan (coordinator), Isabela Atanasiu, "Romanian special development zones and EU state aid policy”, Pre-Accession Impact Studies, European Institute of Romania, www.ier.ro/studiiimpact.html)
Keywords: 330